Obstructive sleep apnea is associated with increased rotor burden in patients undergoing focal impulse and rotor modification guided atrial fibrillation ablation. Issue Volume 20:Issue FI 3(2018) (9th August 2017) - Friedman, Daniel J; Liu, Peter; Barnett, Adam S; Campbell, Kristen Bova; Jackson, Kevin P; Bahnson, Tristram D; Daubert, James P; Piccini, Jonathan P
Abstract: Aims: To assess whether obstructive sleep apnea (OSA) was associated with increased rotor burden among atrial fibrillation (AF) patients. Methods and results: We studied 33 consecutive patients who were scheduled for focal impulse and rotor modulation (FIRM) ablation at our institution to describe the mapping, ablation, and outcomes, among patients with and without OSA. Patients underwent biatrial FIRM mapping in AF with ablation of stable rotors in addition to conventional ablation lesion sets. Differences between groups were tested with student's t -tests and Fisher's exact tests, as appropriate. Survival analyses were performed using the Kaplan–Meier method. Twelve of the 33 (36%) patients had OSA and 8 (66%) used continuous positive airway pressure ventilation (CPAP). Obstructive sleep apnea patients had a higher body mass index (BMI) (33.6 vs. 28.8 kg/m 2, P  = 0.01) and were more commonly on beta blockers (67% vs. 29%, P = 0.03) but were otherwise similar regarding baseline characteristics, medication use, and prior AF treatments, including antiarrhythmic drugs and prior ablation. Focal impulse and rotor modulation mapping demonstrated increased rotor burden in the OSA patients (2.6 ± 0.9 vs. 2.0 ± 1.0, P  =0.03). The increased rotor burden was more evident in the right atrium (RA) (1.0 ± 0.7 vs. 0.5 ± 0.7, P  =0.04 compared with left atrium (1.7 ± 0.8 vs. 1.4 ± 0.7, P  = 0.15). There was no correlation between BMI and total number of rotors ( r  = 0.0961, P  = 0.59). Among the population of patients with OSA, CPAP therapy was associated with a lower number of RA rotors (0.8 ± 0.7 vs. 1.5 ± 0.6, P  = 0.05) but no significant difference in overall rotors ( P  = 0.33). Conclusion: Obstructive sleep apnea patients demonstrate increased rotor prevalence, driven predominantly by an increase in RA rotors. CPAP therapy was associated with fewer RA rotors.